Da filosofia antiga à filosofia contemporânea da acção - Santos, Ricardo (2011)
In this chapter, the author presents and develops his views on the philosophy of action. One main theme is the problem of acrasia: how is it possible that a person sometimes acts freely and intentionally against his own better judgement? The author criticizes Donald Davidson’s solution to this problem for being unrealistic and exaggerating the rationality of the agent. He also presents his original way of reading Aristotle’s most famous text on this subject, in Ethica Nicomachea VII 3. The role of desires and reasons in the motivation of action, the individuation of actions, and the possibility of mental causation are also discussed.